In silico screening of hispolon and its analogs: Pharmacokinetics and molecular docking studies with cyclooxygenase-2 enzyme - Mohadese Mohammadi, Mohammad Firoz Khan, Ridwan Bin Rashid, Sina Mirzaie Nokhostin, Mohammad A. Rashid (Journal of Applied Pharmaceutical Science, 2022)
Hispolon is a phenolic compound with diverse biological activities. The analgesic action of hispolon is due to the inhibition of prostaglandins biosynthesis. However, the molecular basis of this inhibition has not been explored yet. Therefore, we have carried out theoretical investigations to evaluate the molecular basis of analgesic action. Furthermore, we have conducted high throughput in silico screening of a library of compounds to get novel cyclooxygenase 2 (COX-2) inhibitors with better pharmacokinetic and analgesic properties. The docking study was conducted using PyRx and the drug-like properties were calculated by MarvinSketch. Furthermore, the pharmacokinetic properties were computed on the online server PreADMET. In this study, our virtual screening based on structure similarity search using hispolon as reference structure afforded 1,699 compounds. These compounds were subjected to molecular docking with COX-2. These were then filtered based on binding affinity, binding poses, and drug-like properties which yielded seven compounds. The in silico pharmacokinetic study revealed that these compounds possess good human intestinal absorption and moderate permeability. Moreover, molecular docking of these compounds revealed that all the ligands possess moderate to good binding affinity (−7.6 to −8.9 Kcal/mol). Our computed properties may assist in developing hispolon derivatives with better pharmacokinetic and COX-2 inhibitory activity.
Keywords: Hispolon, molecular docking, structure similarity, drug-like properties, pharmacokinetic properties.